PENGARUH PRAHIDROLISIS TERHADAP KUALITAS PULP RAYON ACACIA MANGIUM WILLD - Rena M Siagian; Jefri R S; Bedyaman T; Kayano Purba (Jurnal Penelitian Hasil Hutan, 1989)
Rayon grade pulping trials from Acacia mangium Willd have been studied with variation in pH and prehydrolysis time.Sulphuric. abid, water and sodium hydroxide were used as prehydrolysing agent at pH 4, 7, and 10 each were prehydrolized.for 30,and 60 minutes at 160°C. Following the prehydrolysis, the suphate pulping was conducted by using the active alkali 16%, sulphydity 25%. The maximum temperature was 170°C maintained for 90 minutes. The resulting pulps were bleached by C-E-H-E-H bleaching system and finally acidified with hydrochloric acid.The yield of unbleach pulp ranging from 37- 43% and permanganate number from 8.5 to 10.4.The increase of the prehydrolysing pH from 4 to 10 will decrease alpha cellulose content and viscosity while the beta, gamma cellulose content and alkali solubility tend to increase.The pulping trials under prehydrolysis pH 4 for 60 minutes of Acacia mangium gave the best alpha cellulose yield and lowest hemicellulose and ash content.